2009
DOI: 10.1161/circep.108.812024
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Organization of the Left Atrial Substrate After Circumferential Pulmonary Vein Isolation of Atrial Fibrillation

Abstract: Background-There is a paucity of data regarding the mechanism of maintaining atrial fibrillation (AF) after pulmonary vein isolation (PVI) in patients with AF. The aim of this study was to examine the impact of circumferential PVI on the left atrial (LA) substrate characteristics. Methods and Results-Seventy-two AF patients (age, 53Ϯ11 years) underwent mapping and catheter ablation using an NavX system. The biatrial characteristics such as the complex fractionated atrial electrograms (CFEs; based on fractionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 30 publications
5
115
3
Order By: Relevance
“…20) Thus, given that PV isolation intensively eliminates the FAP areas around the PVs as shown in the present study or previous ones, 8,9) a greater proportion of FAP areas is supposed to be removed by the PV isolation during AF in patients with paroxysmal AF than in those with persistent AF. Accordingly, the patients with persistent AF in whom FAP areas were extensively eliminated after the PV isolation may instead have had an arrhythmogenic substrate close to that characterizing paroxysmal AF.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…20) Thus, given that PV isolation intensively eliminates the FAP areas around the PVs as shown in the present study or previous ones, 8,9) a greater proportion of FAP areas is supposed to be removed by the PV isolation during AF in patients with paroxysmal AF than in those with persistent AF. Accordingly, the patients with persistent AF in whom FAP areas were extensively eliminated after the PV isolation may instead have had an arrhythmogenic substrate close to that characterizing paroxysmal AF.…”
Section: Discussionsupporting
confidence: 69%
“…7) The CFAE area 8,9) and number of GPs 10) both are known to be reduced after PV isolation in patients with persistent AF, and therefore this ablation strategy is presumed to be more than just a trigger elimination. In the present study, we attempted to determine what patients with persistent AF could gain a benefit from PV isolation alone by means of analyzing the alterations in the CFAE and GPs before and after the PV isolation.…”
Section: P Ulmonary Vein (Pv) Isolation Is the Cornerstone Of Cath-mentioning
confidence: 99%
“…In patients in whom AF was not terminated by PVI or in whom sustained AF was inducible after PVI, additional ablation was performed in the LA according to the results of post-PVI complex fractionated atrial electrogram (CFAE) mapping. 18 The endpoint of this ablation step was termination of the AF during the procedure or abolition of all CFAEs in the LA if AF was not terminated. Anti-arrhythmic drugs previously prescribed to the patients were resumed after the procedure but were stopped 6 months later.…”
Section: Hematologic Measurementsmentioning
confidence: 99%
“…CFAEs or high dominant frequency sites have been suggested to be important regions for the initiation and/or the maintenance of AF. 18 CFAEs or high dominant frequency sites are commonly distributed at the PV antrum, LA appendage, mitral annulus, or LA roof. 18 Of interest, these sites were similar to the location of the EAT surrounding the LA.…”
Section: Eat and Afmentioning
confidence: 99%
“…Reprinted with permission from Ref. 32 Nademanee et al reported that CFAE map-guided left atrial (LA) ablation terminated sustained AF in 95% of patients, resulting in excellent clinical outcomes (1 year AF-free rate, 91%) and improved mortality rates [33]. However, the electro-physiologic mechanism of CFAE has not been clearly elucidated yet.…”
Section: Clinical Implicationmentioning
confidence: 99%